Effects of dietary protein level on growth and protein intake of young growing ostriches (Struthio camelus) - Engku Ahmed, Engku Azahan; Mahat, Noraziah (2009)
A study was conducted to evaluate responses in growth and protein intake of confinement-raised young growing ostriches, to three levels of dietary protein (CP). Eighteen ostriches aged between 10 and 14 weeks were used in the study which was conducted over a period of six weeks. The three dietary protein levels investigated were high protein (HP, 22.5% CP), medium protein (MP, 17.5% CP) and low protein (LP, 12.5% CP). All diets contained an equal crude fibre concentration of 11.2%. Ostriches fed on the HP and MP feeds consumed more feed, gained more weight and were more efficient in converting feed to body weight than birds fed on the LP feed. Differences in growth parameters between the HP and MP treatment groups were not significant. Birds on HP feed consumed more protein than those offered the MP feed but this was not translated into superiority in growth. Consumption of protein by the ostriches on the LP feed was significantly lower than by birds on HP or MP feed. Results were discussed and it was concluded that among the three diets studied, a medium protein feed with a CP content of 17.5% was optimum and most economical for growing ostriches.